PENTLANDITE SULFUR CORE ELECTRON BINDING ENERGIES - Goh S.W.; Buckley A.N.; Lamb R.N.; Fan L.; Jang L.; Yang Ya. (My University, 2006)
A number of freshly abraded surfaces of pentlandite have been characterised by X-ray photoelectron spectroscopy to establish whether the initial intensity of the S 2p component near 161.4 eV, previously assigned to the 25% of S atoms in fourfold coordination by metal atoms in pentlandite, was always at least 25% of the total S 2p intensity. It was found that the intensity of this S 2p component could be lower than 20% for surfaces that were not significantly oxidised. To assess whether the proposed 0.75–0.8 eV 2p binding energy difference for the two sulfur environments in pentlandite was justified, ab initio calculations of the difference in core electron binding energies and of the densities of unfilled states have been carried out. The corresponding simulated S K near-edge X-ray absorption fine structure (NEXAFS) spectra have been compared with experimental spectra. The calculated S 2p and S 1s binding energy differences were 0.45 and 0.5 eV at most, in agreement with the experimental NEXAFS spectra. It was concluded that the S 2p component near 161.4 eV arises entirely from violarite present at the pentlandite surface rather than from 4-coordinate S in pentlandite itself. Ab initio calculations of the difference in S 2p binding energies for the 2- and 3-coordinate S in stibnite have also been carried out and found to be quite small, in agreement with previously reported experimental values. Nevertheless, for both pentlandite and stibnite, calculations have confirmed that an increase in coordination number is associated with an increase in sulfur core electron binding energies, even although that increase is barely measurable for the latter sulfide.
Keywords: PENTLANDITE; XPS; NEXAFS; AB INITIO CALCULATIONS; STIBNITE